Phytochemical Constituents of Propolis Flavonoid, Immunological Enhancement, and Anti-porcine Parvovirus Activities Isolated From Propolis - Ma, Xia; Guo, ZhenHuan; Li, Yana; Yang, Kun; Li, Xianghui; Liu, Yonglu; Shen, Zhiqiang; Zhao, Li; Zhang, Zhiqiang (Frontiers in Veterinary Science, 2022)
Propolis is widely used in health preservation and disease healing; it contains many ingredients. The previous study had revealed that the ethanolic or water extracts of propolis have a wide range of efficacy, such as antiviral, immune enhancement, anti-inflammatory, and so on, but its antiviral components and underlying mechanism of action remain unknown. In this study, we investigated the chemical composition, anti-porcine parvovirus (PPV) effectiveness, and immunological enhancement of propolis flavone ethanolic extracts. The chemical composition of propolis flavone was distinguished by ultra-performance liquid chromatography-quadrupole/time-of-flight tandem mass spectrometry analysis. In this study, the presence and characterization of 26 major components were distinguished in negative ionization modes to evaluate the effects of propolis flavonoid used as an adjuvant on the immune response of Landrace–Yorkshire hybrid sows immunized with an inactivated vaccine of PPV. Thirty Landrace-Yorkshire hybrid sows were randomly assigned to one of three groups, and the sows in the adjuvant groups were intramuscularly injected with PPV vaccine with a 2.0-ml propolis flavonoid adjuvant (PA) and oil emulsion adjuvant. After that, serum hemagglutination inhibition antibody titers and specific immunoglobulin (Ig)M and IgG subclasses were measured to evaluate the adjuvant effects of propolis flavonoid on the humoral immune responses, as well as peripheral lymphocyte proliferation activity and serum concentrations of Th1 and Th2 cytokines for cellular immunity. Results indicated an enhancing effect of PA on IgM, interleukins 2 and 4, interferon-γ, and IgG subclass responses. Especially in the effect of improving cellular immune response, the PA was the best. These findings suggested that PA can significantly enhance the immune responses against the PPV vaccine and could be an alternative way to improve PPV vaccination in sows. Furthermore, we screened the PF chemical components to the effectiveness of anti-PPV. Ferulic acid has an excellent anti-PPV effect.